Efficacy and safety of titrated canagliflozin in patients with type 2 diabetes mellitus inadequately controlled on metformin and sitagliptin. Issue 8 (7th June 2016) - Rodbard, H. W.; Seufert, J.; Aggarwal, N.; Cao, A.; Fung, A.; Pfeifer, M.; Alba, M.
Abstract : Aims: To evaluate the efficacy and safety of titrated canagliflozin, a sodium glucose co‐transporter 2 inhibitor, in patients with type 2 diabetes mellitus (T2DM) inadequately controlled on metformin and sitagliptin. Methods: In this randomized, double‐blind study, patients with T2DM (N = 218) on metformin ≥1500 mg/day and sitagliptin 100 mg received canagliflozin 100 mg or placebo. After 6 weeks, the canagliflozin dose was increased from 100 to 300 mg (or from placebo to matching placebo) if all of the following criteria were met: baseline estimated glomerular filtration rate ≥70 ml/min/1.73 m 2 ; fasting self‐monitored blood glucose ≥5.6 mmol/l (≥100 mg/dl); and no volume depletion–related adverse events (AEs) within 2 weeks before dose increase. Endpoints included change in glycated haemoglobin (HbA1c) at week 26 (primary); proportion of patients achieving HbA1c <7.0%; and changes in fasting plasma glucose (FPG), body weight and systolic blood pressure (SBP). Safety was assessed using AE reports. Results: Overall, 85.4% of patients were titrated to canagliflozin 300 mg or matching placebo (mean ± standard deviation time to titration 6.2 ± 0.8 weeks). At week 26, canagliflozin (pooled 100 and 300 mg) demonstrated superiority in HbA1c reduction versus placebo (−0.91% vs. −0.01%; p < 0.001). Canagliflozin provided significant reductions in FPG, body weight and SBP compared with placebo (p < 0.001). The overall AE incidence was 39.8 and 44.4% for canagliflozin and placebo, respectively. Canagliflozin was associated with an increased incidence of genital mycotic infections. Conclusions: Titrated canagliflozin significantly improved HbA1c, FPG, body weight and SBP, and was generally well tolerated over 26 weeks in patients with T2DM as add‐on to metformin and sitagliptin.